EFEKTIFITAS TUMBUHAN ENCENG GONDOK (EICHORMONIA CRASSIPES) SEBAGAI FITOREMEDIASI DALAM MENURUNKAN KADAR BESI (Fe), TIMAH HITAM (Pb), MANGAN (Mn) PADA LEACHATE TPA - Suryanti, Septiana (JURNAL MEDIA KESEHATAN, 2013)
This study aims at knowing the difference in decreased levels of iron (Fe), lead (Pb), and manganese (Mn) in leachate before and after treatment. Research used a true experimental design with pre-post test design. The amount of leachate that is used in each treatment is 10 liters of leachate and 1 kg of water hyacinth, and do in 3 times repetition. Analysis of the was tested using One Way ANOVA test followed by LSD (Least Significance Difference). The results showed that there were significant differences in the use of water hyacinth in the leachate decreased levels of iron (Fe), lead (Pb), and manganese (Mn) with a value of ρ = 0.000. Research results before treatment (pre-test) levels Fe = 6.30 mg / l, after treatment (post-test) Fe = 0.25 mg / l, before treatment (pre-test) value Pb = 2.90 mg / l, after treatment (post-test) and Pb = 0.33 before treatment (pre-test) the value of Mn = 2.68 mg / l, after treatment (post-test) Mn = 0.08 mg / l. It is known that the ability of water hyacinth weighing 1 kg with a time of 6 days is more effective than water hyacinth 2 days and 4 days in the lower levels of iron (Fe), lead (Pb) and manganese (Mn) in the leachate. It can be concluded that water hyacinth could reduce levels of iron (Fe), lead (Pb) and manganese (Mn) in the leachate with contact time 6 days.